Environmental Aspects of Participatory Budgeting in Selected Cities in Europe - SIEMIONEK-RUSKAŃ, Małgorzata; SIEMIONEK-LEPCZYŃSKA, Anna (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025, 2025)
This paper explores the integration of environmental priorities into participatory budgeting (PB) processes in selected European cities, with a focus on Poland, Spain, and Portugal. Participatory budgeting enables citizens to directly influence how municipal funds are allocated, providing a democratic platform for the development of sustainable urban projects. Through a review of literature and case studies, the paper examines how PB contributes to environmental initiatives such as green infrastructure, waste management, energy efficiency, sustainable transport, and climate resilience. Case studies from Warsaw and Gdańsk in Poland, Barcelona and Valencia in Spain, and Lisbon and Porto in Portugal illustrate the diverse ways cities have used PB to fund projects like community gardens, green roofs, riverbank restoration, and bike infrastructure. These initiatives not only address local ecological challenges but also promote civic engagement, environmental justice, and long-term sustainability. The findings highlight the transformative potential of participatory budgeting as a tool for inclusive urban governance and environmental planning in selected European cities. The main objective is to examine how PB can serve as a democratic tool for environmental governance, promoting sustainability, resilience, and citizen engagement. The study adopts a qualitative case study approach supported by literature review and document analysis. It evaluates municipal participatory budgeting initiatives with a specific focus on green infrastructure, waste management, energy efficiency, sustainable mobility, and climate adaptation. Academic sources, city budget reports, and environmental planning documents were analyzed to identify the environmental impact and governance models of PB in each city. Participatory budgeting in European cities increasingly funds environmental projects, such as green roofs, urban gardens, tree planting, sustainable transport, and flood prevention. The active involvement of citizens in decision-making ensures that environmental solutions are locally relevant, socially inclusive, and ecologically impactful. Results show that PB contributes to improved urban resilience, environmental justice, and long-term sustainability by aligning ecological goals with democratic processes. This study is among the first to comparatively examine environmental projects under PB frameworks in Eastern and Southern Europe. It offers new insights into how participatory governance mechanisms can shape urban environmental policy and increase community ownership of green transitions. Policymakers and city planners can use participatory budgeting as a strategic instrument for environmental planning, ensuring that public investments are both citizen-driven and environmentally sound. The paper provides examples and recommendations for replicating successful PB-based environmental initiatives across diverse urban contexts.